2005
DOI: 10.1074/jbc.m506863200
|View full text |Cite
|
Sign up to set email alerts
|

M-RIP Targets Myosin Phosphatase to Stress Fibers to Regulate Myosin Light Chain Phosphorylation in Vascular Smooth Muscle Cells

Abstract: Vascular smooth muscle cell contraction and relaxation are directly related to the phosphorylation state of the regulatory myosin light chain. Myosin light chains are dephosphorylated by myosin phosphatase, leading to vascular smooth muscle relaxation. Myosin phosphatase is localized not only at actin-myosin stress fibers where it dephosphorylates myosin light chains, but also in the cytoplasm and at the cell membrane. The mechanisms by which myosin phosphatase is targeted to these loci are incompletely unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
72
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(84 citation statements)
references
References 52 publications
12
72
0
Order By: Relevance
“…3B) or by mRNA analysis (MRIP; 85-95% decrease of mRNA levels in three separate experiments). As expected from previous studies (Koga and Ikebe, 2005;Surks et al, 2005;Xia et al, 2005), siMRIP or siMYPT1 transfections alone increased the number of actin fibers (data not shown; see also Fig. 6A-D).…”
Section: Nuak2 Targeted To Actin Stress Fibers By Mripsupporting
confidence: 76%
See 2 more Smart Citations
“…3B) or by mRNA analysis (MRIP; 85-95% decrease of mRNA levels in three separate experiments). As expected from previous studies (Koga and Ikebe, 2005;Surks et al, 2005;Xia et al, 2005), siMRIP or siMYPT1 transfections alone increased the number of actin fibers (data not shown; see also Fig. 6A-D).…”
Section: Nuak2 Targeted To Actin Stress Fibers By Mripsupporting
confidence: 76%
“…Although treatment with the ROCK inhibitor Y27632 leads to rapid disassembly of actin stress fibers in normal cells, in MRIPdownregulated cells Y27632-mediated fiber loss is significantly impaired (Surks et al, 2005), which was suggested to reflect the inability of MYPT1 and MLCP to target to fibers. To investigate disassembly of actin stress fibers upon ROCK inhibition in NUAK2-expressing cells they were treated with 10 M Y27632 for 30 minutes and analyzed for actin fibers.…”
Section: Nuak2 Expression Renders Central Actin Stress Fibers Resistamentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect it is interesting that phosphorylation of T855 reduces binding of myosin [8]. Another view is that the cell localization of myosin II could involve another protein, such as M-RIP (aka p116RIP) [9].…”
Section: Properties Of Mypt1mentioning
confidence: 99%
“…For RhoA activation, GTP-bound RhoA was measured by using GST-Rhotekin-RBD binding assays as described (32). For determination of RhoA-S188-PO 4, WT and LZM VSMC lysates were resolved by SDS/PAGE and immunoblotted with anti-RhoA-S188-PO 4 antibodies in standard fashion, as described in SI Text.…”
Section: Rt-pcrmentioning
confidence: 99%